Investigating causes and consequences of purchase intention of luxury fashion - Suha, F. S.; Chaichi, Kamelia * (Growing Science, 2018)
The purpose of this study is to examine the influences of self-identity, subjective norm and attitude on the intention to purchase luxury fashion goods. It also demonstrates how purchase intention influences on customers' intention to pay premium prices for luxury fashion goods. A theoretical model is established and assessed in this study on a sample of luxury fashion consumers in Malaysia. By means of a self-structured questionnaire, 240 valid submissions are included for data analysis with the Smart-PLS software 3.2.0. The results support all hypotheses on the correlation of self-identity, subjective norm and attitude with purchase intention and price premium, except the correlation between self-identity and purchase intention. This is the first research paper investigating self-identity as an antecedent of purchase intention, and price premium as a consequence of purchase intention. It also justifies the behavior of luxury fashion consumers with regards to luxury fashion products. Findings from this study may help marketers develop effective strategies which would yield them a competitive advantage within the luxury fashion market.